Community capitalism in China : the state, the market, and collectivism - Hou, Xiaoshuo, 1982- (Cambridge University Press, 2013)
"This book proposes to end the dichotomous view of the state and the market, and capitalism and communism, by examining the local institutional innovation in three villages in China and presents community capitalism as an alternative to the neoliberal model of development. Community is both the unit of redistribution and the entity that mobilizes resources to compete in the market; collectivism creates the boundary that sets the community apart from the outside and justifies and sustains the model. Community capitalism differs from Mao-era collectivism, when individual interests were buried in the name of collective interests and market competition was not a concern. It also deviates from cooperatives such as Israeli kibbutzim in that there are obvious hierarchies in the community and people pursue the accumulation of wealth and modern conveniences. Nonetheless, this book demonstrates the embeddedness of the market in community, showing how social relations, group solidarity, power, honor, and other values play an important role in these villages' social and economic organization."--Publisher's website